Impact of subway shield tunnel construction on deformation of existing utility tunnel - Wei, Shi; Zenglin, Hong; Min, Yang; Ning, Li; Tianxiang, Tan (Frontiers in Earth Science, 2023)
In recent years, the development of urban underground space in China, especially the construction and operation of subway tunnels, has greatly relieved the pressure of urban traffic. Due to the imperfect planning of urban facility, many subway tunnels have to be built under the existing utility tunnels (pipe galleries). Nevertheless, shield construction of subway tunnel has a great adverse impact on the deformation and safety of the existing pipe gallery. Therefore, this paper takes Xi’an Metro Line 2 as an example, and studies the safety depth for subway tunnel shield construction under different regional conditions in Xi’an through numerical simulation. The results show that the deformation of the existing pipe gallery and its influence range decrease with the rising buried depth of the double-line subway tunnel when the soil properties are good. For example, in the loess tableland area, when the buried depth of the subway tunnel is greater than 12 m, the settlement deformation of the pipe gallery basically meets the control standard. When the soil properties are poor or the soil properties vary greatly, the subway tunnel excavation has a great impact on the safety of the pipe gallery. For example, in the first-level alluvial fan area with sand layer, when the buried depth of the subway tunnel is less than 24 m and more than 12 m, the deformation standard cannot be satisfied. In addition, in the first-level alluvial fan area with sand layer, the lower soil layer should be treated or the construction parameters should be optimized before the excavation of subway tunnel. The research results can provide reference for similar engineering construction.